5 penggerak bangsa yang terlupa : nasionalisme minoritas Kristen / Gerry Van Klinken ; penerjemah, Ammiruddin ; editor, Helmi Mustafa & Muhammad Al-Fayyadl. - KLINKEN, GERRY VAN; Amiruddin; Helmi Mustafa; Muhammad Amiruddin (LKiS, 2012)
ix, 414 hlm. ; 21 cm (3 eks.)